2020
DOI: 10.1016/j.brs.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta-burst stimulation moderates interaction between increment of N-Acetyl-Aspartate in anterior cingulate and improvement of unipolar depression

Abstract: a b s t r a c tBackground: Intermittent theta-burst stimulation (iTBS), a novel repetitive transcranial magnetic stimulation (rTMS) technique, appears to have antidepressant effects when applied over left dorsolateral prefrontal cortex (DLPFC). However, its underlying neurobiological mechanisms are unclear. Proton magnetic resonance spectroscopy ( 1 H-MRS) provides in vivo measurements of cerebral metabolites altered in major depressive disorder (MDD) like N-acetyl-aspartate (NAA) and choline-containing compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…When ACC is damaged, it will produce many clinical symptoms, including inattention, dysfunction of autonomic function regulation, emotional instability ( 35 , 36 ). Studies have found that the ACC is prone to damage in depression ( 37 , 38 ). Structural magnetic resonance study found that the anterior cingulum white matter fibrosis of the ACC recovered after 8 weeks of antidepressant treatment ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…When ACC is damaged, it will produce many clinical symptoms, including inattention, dysfunction of autonomic function regulation, emotional instability ( 35 , 36 ). Studies have found that the ACC is prone to damage in depression ( 37 , 38 ). Structural magnetic resonance study found that the anterior cingulum white matter fibrosis of the ACC recovered after 8 weeks of antidepressant treatment ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ mean age ranged from 15.5 to 53 years across studies, with an overall mean ± SD age of 36.8 ± 11.3. Age composition varied and included studies of adolescents (ages 13–17 ( Croarkin et al, 2016 )), adolescents to young adults (ages 15–21 ( Yang et al, 2014 )); and young adults (ages 18–40 ( Zheng et al, 2015 , Zheng et al, 2010 )), with most studies (8/12) focusing on adult patients (ages 20–70 ( Baeken et al, 2017 , Dubin et al, 2016 , Luborzewski et al, 2007 , Erbay et al, 2019 , Zavorotnyy et al, 2020 , Godfrey et al, 2021 , Levitt et al, 2019 , Bhattacharyya et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of two studies which included a small number of participants with a primary diagnosis of bipolar II or bipolar I disorder ( n = 3) ( Dubin et al, 2016 , Godfrey et al, 2021 ), participants had a primary diagnosis of current MDD using standard Diagnostic and Statistical Manual of Mental Disorders (DSM) DSM-IV, DSM-IV-TR or DSM 5 criteria ( American Psychiatric Association, 2013 , American Psychiatric Association, 2000 ). Some level of pharmacoresistance characterized the participants in nine studies; one study did not specify participants’ past treatment history or pharmacoresistance ( Zavorotnyy et al, 2020 ), and two did not require treatment resistance ( Luborzewski et al, 2007 , Erbay et al, 2019 ). Information on psychiatric comorbidities was available in five studies and included secondary diagnoses of attention deficit hyperactivity disorder, obsessive compulsive disorder, generalized anxiety disorder, social phobia, and post-traumatic stress disorder ( Croarkin et al, 2016 , Yang et al, 2014 , Dubin et al, 2016 , Erbay et al, 2019 , Godfrey et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, DESI-MSI showed that the N-acetyl aspartic acid ( m / z = 174.04) and L-glutamine ( m / z = 145.06) levels were increased in the brain of 10-month-old BChE KO mice ( Figure 9 A–E). N-acetyl aspartic acid is synthesized in neuronal mitochondria and transported via axons, its cerebral level correlates with the number of neurons, and is as a putative marker for health, viability, and/or number of neurons [ 50 ]. The level of N-acetyl aspartic acid is reduced in the brain of AD patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased of L-glutamine in the brain of BChE KO mice in this study is consistent with our previous publication in which BChE inhibition restored the decreased of L-glutamine in Aβ-42-induced astrocytes [ 30 ], and the glutamate–glutamine cycle has a pivotal role in the etiology of AD [ 53 ]. Studies also have found that the increase of L-glutamine and N-acetyl aspartic acid can reduce the risk of depression [ 50 , 54 ].…”
Section: Discussionmentioning
confidence: 99%